2018
DOI: 10.1007/s10096-017-3179-1
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotype and viral load agreement between paired first-void urine and clinician-collected cervical samples

Abstract: The performance and acceptability of first-void urine as specimen for the detection of HPV DNA in a Belgian referral population was evaluated using an optimized sample collection and processing protocol. One hundred ten first-void urine and cervical samples were collected from 25- to 64-year-old women who were referred for colposcopy (January–November 2016). Paired samples were analyzed by the Riatol qPCR HPV genotyping assay. Acceptability data were gathered through questionnaires (NCT02714127). A higher high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
47
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 49 publications
14
47
0
1
Order By: Relevance
“…Thus, the lower hrHPV positivity in urine may be due to specimen type differences rather than the assay itself [15]. Our result corresponds to most comparative studies [9-12, 15, 28, 29], but not all [13,14,27].…”
Section: Interpretation and Comparison With Previous Studiessupporting
confidence: 84%
See 4 more Smart Citations
“…Thus, the lower hrHPV positivity in urine may be due to specimen type differences rather than the assay itself [15]. Our result corresponds to most comparative studies [9-12, 15, 28, 29], but not all [13,14,27].…”
Section: Interpretation and Comparison With Previous Studiessupporting
confidence: 84%
“…In comparison, invalid test rates of urine samples have in other studies been reported to range between 0 and 4% using PCRbased HPV DNA assays [9,10,[12][13][14][15]29]. Whether optimizing the (pre)-analytical processing protocols could lead to better results for the CLART assay warrants further exploration.…”
Section: Interpretation and Comparison With Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations